Impaired emotion processing and a reduction in trust in patients with somatic symptom disorder. (18th October 2017) - Erkic, Maja; Bailer, Josef; Fenske, Sabrina C.; Schmidt, Stephanie N. L.; Trojan, Jörg; Schröder, Annette; Kirsch, Peter; Mier, Daniela
Abstract : There is accumulating evidence for deficits in the perception and regulation of one's own emotions, as well as the recognition of others' emotions in somatic symptom disorder (SSD). However, investigations of SSD focusing on specific aspects of emotion processing and how these might interact are missing. We included 35 patients with SSD and 35 healthy controls who completed questionnaires on the perception and regulation of their own emotions, as well as experimental investigations of emotion recognition and trust. In line with previous studies, our results show that SSD patients in comparison to healthy controls have difficulties in the identification and description of own feelings (η p 2  = .381 and η p 2  = .315). Furthermore, we found that patients apply less cognitive reappraisal (η p 2  = .185) but tend to use more expressive suppression (η p 2  = .047). In contrast to previous studies, we found SSD patients to perform superior in emotion recognition, in particular for anger ( d  = 0.40). In addition, patients with SSD invested less in a trust game ( d  = 0.73). These results point to a higher sensitivity for negative emotions and less trust in others. Further, these findings suggest a dissociation between the ability to recognize one's own emotions versus others' emotions in SSD. Future interventions targeting emotion processing in SSD might focus on the identification of one's own emotions, prior to the training of emotion regulation.